Pengaruh Perubahan Ekonomi Global Terhadap Perkembangan Hukum Di Indonesia - Dewi, Yunica Kusuma (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2021)
Various problems regarding the improvement of the Indonesian economy have arisen due to changes in the global economy. Economists recommend that economic cooperation with the international community be increased, especially with ASEAN countries. This is important to harmonize the development of the world economy with the economic development of ASEAN countries full of competition. There are also those who argue that Indonesia's economic development so far has not favored the people's economy, and it is also necessary to create a development strategy by involving the people more in various economic and trade fields. Conceptually, this article aims to find out: changes in the global economy in Indonesia, and the effect of global economic changes on legal developments in Indonesia. Using Lawrence M. Friedman's theory which states that the law is not autonomous, but on the contrary, the law is open at all times to outside influences, this research produces findings, with changes in the global economy, the law in Indonesia has changed functions, including 1) standards of conduct, 2) as a tool of social engineering, 3) as a tool of justification, 4) as a tool of control, 5) rechtszekerheid